Khiyar, Consumer Protection, and Production Continuity in e-Commerce Transactions: Hadith Perspective - Peti Savitri (Journal of Islamicate Studies, 2020)
This article discusses Hadith narrated by Hakim b. Hizam about Khiyar in sahih al-Bukhari which is associated with consumer protection and production continuity in a modern buying and selling transaction which is often referred to as e-commerce or online shopping as is happening in this digital era. This article was written using the Takhrij al-hadits method. The data source is in the form of a narration of the Hadith in sahih al-Bukhari about Khiyar. The type of data is in the form of hadith text in sahih al-Bukhari about Khiyar complete sanad and matn. The data collection technique is done by tracing the Hadith narration about Khiyar sahih al-Bukhari. The data analysis technique was carried out by applying the Shara al-hadits method, both in the sanad and matn aspects. This article reveals that the hadith narrated by Hakim b. Hizam about Khiyar in sahih al-Bukhari relates to the concept of consumer protection and continuity of production